THE RELATIONSHIP BETWEEN ANTECEDENT AND CONSEQUENCE FACTORS WITH SAFETY BEHAVIOUR IN PT.X - Fitriani, Apris; Nawawiwetu, Erwin Dyah (Faculty of Vocational Studies, Universitas Airlangga, 2017)
Background : Safety behaviour is an act worker to minimize the possibility of accidents in workplace. Based on the Antecedents-Behaviour-Consequence (ABC) theory, safety behaviour of worker related with the antecedent and consequence factors. Purpose: The purpose of this research was to study the association between antecedent and consequence factors with safety behaviour of workers in Ring Frame Unit Spinning II PT. X. Method: This was an observational descriptive research with cross sectional approach. Sample size was the total population 24 workers. The variables studied were level of knowledge, motivation, perception, private problem, OSH regulation, availability of safety facilities, frequency of OSH training, controlling, positive reinforcement (reward), and negative reinforcement (punishment). The strength of relationship between variables dependent and independent were analyzed by using Contingency Coefficient (C). Result: The results showed that there were strong association between motivation, private problem, frequency of OSH training, positive reinforcement (reward), and negative reinforcement (punishment) with safety behaviour (C = 0.622, C = 0.508, C = 0.702, C = 0.669, dan C = 0.707, respectively). There were very strong association between knowledge, perception, OSH regulation, and controlling with safety behaviour (C = 0.763, C = 0.797, C = 0.768, dan C = 0.797, respectively). Conclusion: the higher the knowledge and motivation to work safely the higher the safety behaviour of the workers would be. Workers who have not personal problem, have already participated in OSH training, feeling supervised and given reward and punishment applied higher safety behaviour.